2017
DOI: 10.3390/ijms18102109
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 1 and Sphingosine-1-Phosphate Signaling in Colorectal Cancer

Abstract: Sphingosine kinase 1 (Sphk1) is a highly conserved lipid kinase that phosphorylates sphingosine to form sphingosine-1-phosphate (S1P). Growing studies have demonstrated that Sphk1 is overexpressed in various types of solid cancers and can be induced by growth factors, cytokines, and carcinogens, leading to the increase of S1P production. Subsequently, the increased Sphk1/S1P facilitates cancer cell proliferation, mobility, angiogenesis, invasion, and metastasis. Therefore, Sphk1/S1P signaling plays oncogenic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…SPHK1 and UGGT2 were significantly upregulated in CRC tissues. This result is in accordance with those of recent studies that indicated that SPHK1 is overexpressed and serves an important role in tumorigenesis, proliferation, invasiveness and metastasis in CRC (42,43). On the other hand, HPGD, LPAR1, NAAA, SMPD1 and SMPDL3A were all significantly downregulated in CRC tissues.…”
Section: Discussionsupporting
confidence: 93%
“…SPHK1 and UGGT2 were significantly upregulated in CRC tissues. This result is in accordance with those of recent studies that indicated that SPHK1 is overexpressed and serves an important role in tumorigenesis, proliferation, invasiveness and metastasis in CRC (42,43). On the other hand, HPGD, LPAR1, NAAA, SMPD1 and SMPDL3A were all significantly downregulated in CRC tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Chronic intestinal inflammation has been linked to colorectal cancer and reports demonstrated that S1P mediates pro-inflammatory cytokines such as TNF-α [233,234].…”
Section: A Role Of S1p In Gastrointestinal Diseasesmentioning
confidence: 99%
“…A number of therapeutics have been developed to target components of this pathway for cancer treatment (23,24). Specifically, studies have shown the importance of SPHK1 signaling in cancer metastasis with the likely involvement of EMT (25)(26)(27). Nevertheless, the mechanism by which S1P signaling affects EMT remains to be elucidated.…”
mentioning
confidence: 99%